Organocatalytic Synthesis of γ-Amino Acid Precursors via Masked Acetaldehyde under Micellar Catalysis - Casacchia, Maria Edith; Giorgianni, Giuliana; Allegritti, Elena; Giansanti, Luisa; Carlone, Armando; Pesciaioli, Fabio (SynOpen, 2023)
The development of micellar catalysis offers a sustainable alternative to organic solvents, and represents an environmental milestone in organic synthesis. Here, the first Michael addition of masked acetaldehyde under neutral, cationic and anionic micellar catalysis is reported, affording the products in high yields and enantiomeric excess, despite the use of water as solvent.
Keywords: micellar catalysis; aminocatalysis; asymmetric synthesis; γ-amino acids; green chemistry